Actinidia strigosa Hook. f. & Thomson (Actinidiaceae): A Future Plant with Higher Economic Importance in Hilley-Barsey Sanctuary, Sikkim, India - Padhan, Abhilash; Thakur, Dinesh Singh; Ambrish, Kumar; Mallick, Samarendra Narayan; Dangi, Girish (International Journal of Economic Plants, 2024)
The present study was conducted during the period August, 2021 to March, 2023 in Sikkim state of Northeast India. Actinidia strigosa Hook. f. & Thomson (Theki Phal/wild kiwifruit) is a temperate climbing shrubby plant species, collected from the Hilley-Barsey Sanctuary, West Sikkim, India. It has been observed that this plant is associated with the daily needs of the locals and used for various economic purposes, such as fresh fruit for table purposes, fodder, medicine, and for the preparation of fruit wine. During the field survey in 2021, the plant species A. strigosa was collected from Ribdi (2203 m) to Hilley (2679 m) within the Hilley-Barsey Sanctuary for further study. The distribution of Actinidia strigosa is confined to the Eastern Himalayas, specifically in Sikkim (West, South and East districts), West Bengal (Darjeeling hills), and eastern Nepal, at an altitudes of 2100-2600 m. It has the potential to be used in the kiwifruit breeding industry as gene source to enhance cold tolerance and expand kiwifruit cultivation to high altitudes in the Himalayan regions. Due to its economic importance and limited distribution, conservation is essential, as the plant is vulnerable to uprooting and injury, especially in areas like the Hilley-Barsey Sanctuary in West Sikkim. Being endemic to its area of occurrence with maximum diversity in its morphology at Hilley-Barsey Rhododendron Sanctuary, West Sikkim, the sanctuary must be recognised a biodiversity hotspot for A. strigosa.